The main predictive factors of worse outcome in patients with COVID-19 infection hospitalized in temporary COVID hospital - Djurdjevic, Jovana; Tomonjic, Nina; Cirkovic, Andja; Lukovic, Sretko; Pavlovic, Luka; Rasic, Melanija; Perovic, Marko; Banko, Ana; Jeremic, Ivica (The Journal of Infection in Developing Countries, 2023)
Introduction: After the Serbian community hospitals had reached their full capacity during the pandemic, new institutions were enrolled into the coronavirus disease 2019 (COVID-19) system as temporary COVID hospitals (TCH). These hospitals usually had no intensive care units (ICU) and no possibility to treat severely ill patients. The aim of this study was to identify risk factors at the time of triage that could help identify patients that will require ICU treatment and cannot be treated in a TCH. Methodology: In this retrospective study, a total of 158 patients with COVID-19 infection were enrolled. The demographic information, underlying comorbidities, laboratory findings, chest X-rays, computed tomography scans, and clinical outcomes were obtained from medical records. Deterioration of a patient’s condition was regarded as a need for further transfer to ICU. Results: During the hospitalization 15.2% of patients required transfer to ICU. Patients with deterioration were significantly older and there was no difference between genders. We observed a higher prevalence of hypertension, other cardiovascular diseases, lower lymphocyte and platelet counts, and higher IL-6 and troponin T in patients with deterioration. The multivariate logistical regression model showed that only age was an independent risk factor for deterioration and with each year of age, the risk for poor outcome increased by 8%. Conclusions: Patients with cardiovascular risk factors, low lymphocyte and platelet counts, high IL-6 and troponin T and, especially, increased age should not be treated in a TCH because of the high possibility for deterioration and need for transfer to an ICU.